Dear Cary : my life with Cary Grant - Cannon, Dyan. (New York : itbooks, 2011)
The author wasn't looking for romance when she sat down for lunch with Cary Grant in the studio canteen; she was a young actress on the outskirts of Hollywood just hoping for her big break. What she found was a star-crossed soul mate, a man who fell instantly in love with her, pursued her relentlessly, and eventually persuaded her to love him back equally. She and Cary Grant were a glamorous and popular pair, the epicenter of chic and swinging 1960s Hollywood. For a few brief years their romance flourished; they loved big, married, and had a daughter. In many ways their romance played out like one of Grant's movies: bold, witty, full of dramatic gestures, and equally tender moments. When the love ended, it ended in the same way it had started: dramatically. This was on courthouse steps and on the front page of every newspaper in the world. Completely candid and honest, readers will learn of a side of Cary Grant never before seen.
Keywords: Grant, Cary, -- 1904-1986.; Grant, Cary, -- 1904-1986 -- Marriage; Cannon, Dyan; Cannon, Dyan -- Marriage; Motion picture actors and actresses -- United States -- Biography; Wives -- United States -- Biography